Primary healthcare policy implementation in the Eastern Mediterranean region: Experiences of six countries. (1st January 2018) - van Weel, Chris; Alnasir, Faisal; Farahat, Taghreed; Usta, Jinan; Osman, Mona; Abdulmalik, Mariam; Nashat, Nagwa; Alsharief, Wadeia Mohamed; Sanousi, Salwa; Saleh, Hassan; Tarawneh, Mohammed; Goodyear-Smith, Felicity; et al.
Abstract: Background: Primary healthcare (PHC) is essential for equitable access and cost-effective healthcare. This makes PHC a key factor in the global strategy for universal health coverage (UHC). Implementing PHC requires an understanding of the health system under prevailing circumstances, but for most countries, no data are available. Objectives: This paper describes and analyses the health systems of Bahrain, Egypt, Lebanon, Qatar, Sudan and the United Arab Emirates, in relation to PHC. Methods: Data were collected during a workshop at the WONCA East Mediterranean Regional Conference in 2017. Academic family physicians (FP) presented their country, using the WONCA framework of 11 PowerPoint slides with queries of the country demographics, main health challenges, and the position of PHC in the health system. Results: All six countries have improved the health of their populations, but currently face challenges of non-communicable diseases, aging populations and increasing costs. Main concerns were a lack of trained FPs in community settings, underuse of prevention and of equitable access to care. Countries differed in the extent to which this had resulted in coherent policy. Conclusion: Priorities were (i) advocacy for community-based PHC to policymakers, including the importance of coordination of healthcare at the community level, and UHC to respond to the needs of populations; (ii) collaboration with universities to include PHC as a core component of every medical curriculum; (iii) collaboration with communities to improve public understanding of PHC; (iv) engagement with the private sector to focus on PHC and UHC.